Histopathological Condition of the Remaining Tissues after Endodontic Infection of Rat Immature Teeth - Tobias Duarte, Paulo Carvalho [UNESP]; Gomes Filho, João Eduardo [UNESP]; Ervolino, Edilson [UNESP]; Sundefeld, Maria Lucia Marçal Mazza [UNESP]; TadahiroWayama, Marcelo [UNESP]; Lodi, Carolina Simonetti [UNESP]; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Elsevier B.V., 2014)
Introduction: Recently, case reports have shown that immature teeth diagnosed with necrotic pulp and periapical periodontitis can be repaired through a regenerative endodontic procedure. True regeneration depends on the presence of stem cells in the remaining vital tissues. The aim of this study was to evaluate the histologic condition of the pulp tissue, root apical papilla, and periapical tissues after inducing endodontic infection in immature rat teeth for different periods. Methods: This study evaluated 18 first upper rat molars (36 roots). Periapical lesions were induced and were confirmed radiographically, and the animals were divided into 3 groups according to the days of pulp exposure for endodontic infection induction: 30, 60, and 90 days. Histologic analysis was performed in 5 different areas (ie, cervical, middle, and apical root canal thirds; the apical papilla; and the periapex surrounding the apical papilla). Results: At 30 days, one third of the specimens still showed vital but intensely inflamed pulp tissue in the apical third and vital apical papilla with varying degrees of inflammation. After 60 days, the results were similar with respect to the apical pulp tissue and apical papilla. Completely necrotic pulp tissue in the space canal and vital apical papilla were observed in about 67% of the cases after 90 days. Conclusions: Vital pulp tissue was observed in the apical third until 60 days and in the vital apical papilla until 90 days of infection in a rat model.
Keywords: Endodontic infection; immature nonvital teeth; periapical lesion; regeneration